56 Educational interventions for improving knowledge of dementia progression and the mental health of family carers: a systematic review. Issue 3 (1st September 2017) - Lee, Cheuk Yan; Moore, Kirsten; Candy, Bridget; Sampson, Liz
Abstract : Aim: Dementia is one of the common causes of death worldwide. The progressive nature of dementia can cause chronic grief among caregivers, increasing the risk of developing persistent complex bereavement disorder (DSM 5, 2013). According to the European Association of Palliative Care (EAPC) white paper (2014), education on the progression of dementia should be provided to the family of an individual with dementia. This systematic review aims to examine the effect of educational interventions focusing on providing information regarding the progression of dementia to informal caregivers. Method: MEDLINE, PsycINFO and CINAHL were searched in March 2017. Randomised controlled trials (RCTs) with samples of informal carers who are providing day-to-day caring for an individual with dementia living in the community were eligible. Included interventions were educational programmes that involve a component aimed to increase carer's understanding of the progression of dementia. Two authors independently assessed studies for eligibility. Risk of bias of included studies will be assessed independently by two authors. Results: We screened 2781 citations and 16 studies were included. Preliminary results suggest that educational interventions may improve knowledge of dementia among carers, and may reduce depression. Reduction in carer burden and stress was also reported in some studies. Conclusion: This is the first systematic review to consider the potential benefit of recommendations in the EAPC white paper. Based on these preliminary results, prior to full critique and review analysis, there is some evidence from individual studies to support the effectiveness of educational intervention in improving carers' knowledge in dementia. References: . Van der Steen, J. T., Radbruch, L., Hertogh, C. M., de Boer, M. E., Hughes, J. C., Larkin, P., & Koopmans, R. T. (2014). White paper defining optimal palliative care in older people with dementia: a Delphi study and recommendations from the European Association for Palliative Care. Palliative medicine, 28(3), 197–209. . American Psychiatric Association. (2013). Diagnostic and statistical manual of mental disorders (DSM-5®) . American Psychiatric Pub.